The Influence of TOE Factor and Entrepreneurial Orientation on Social Media-related Performance: The Mediating Role of Innovation Capability and CRM Capability, and the Role of Moderation of Social Media Adoption - Ningrum, Nilawati Puspita; Pusparini, Elok Savitri (PT Mattawang Mediatama Solution, 2025)
This study aims to analyze the influence of TOE Factor and Entrepreneurial Orientation on the Social Media-relayed Performance of multi-industry MSMEs in the Greater Jakarta area, considering the mediating role of Innovation Capability, and CRM Capability, as well as the role of Social Media Adoption moderation. MSMEs were chosen because of their significant role in the national economy, but still face challenges in optimizing digital technology, especially social media. This study uses a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, and involves 243 respondents from multi-industry MSME actors in the Greater Jakarta area to answer surveys distributed online and offline. The results showed that Innovation Capability significantly mediated the relationship between TOE Factor and Social Media-related Performance, and CRM Capability significantly mediated the relationship between Entrepreneurial Orientation and Social Media-related Performance. In contrast, Social Media Adoption does not play a significant role as a moderator in strengthening relationships between variables. These findings make a theoretical contribution to the development of the Dynamic Capability Theory and TOE framework by emphasizing the importance of organizational readiness and strategic orientation in building customer-based digital capabilities. Practically, these results emphasize that the digitalization of MSMEs is not enough just with social media adoption, but requires structural readiness, entrepreneurial leadership, and a consistent customer management system. This research also provides relevant managerial implications for MSME owners, policymakers, and business training and mentoring providers.